EFFECTS OF SELECTED MACROECONOMIC FACTORS ON STOCK RETURN IN THE NIGERIAN STOCK MARKET (1998-2019) - Segun Kamoru FAKUNMOJU; Ibrahim Bello ABDULLAHI; Isaac Olukayode FASOLA (Malete Journal of Accounting and Finance)
The nexus between stock return and macroeconomic indicators have been a debatable phenomenon for a long time. It has also be one of the major issues for domestic and foreign investors in building efficient and optimum stock portfolio in the capital market. However, the unstable macroeconomic indicators adversely affect the level of stock return in the Nigerian capital market. Against this background, this study investigates the effect of macroeconomic factors on stock return in the Nigerian capital market. The study employed secondary data obtained from Nigeria Stock Exchange (NSE) fact book and Central Bank of Nigeria (CBN) statistical bulletin within the period of 1998 to 2019. The data obtained was subjected to Autoregressive Distribution Lag (ARDL) method of analysis. Findings revealed that money supply and aggregate industrial production positively and significantly affect stock return with co-efficient and P-value at (β=0.466098, P<0.05; β=0.213141, P<0.05) while exchange and inflation rates negatively affect stock return in the Nigerian stock exchange market with co-efficient and P-value at (β=-0.009285, P<0.05; β=-0.028260, P<0.05) respectively. The study concludes that macroeconomic factors significantly affect stock return in the Nigerian stock market at both the short run and long run. The study recommends that the Central Bank of Nigeria should employ deflationary fiscal policy and Adaptive Stabilization Method of Exchange Rate policy in order to reduce variance between actual and expected stock returns in the Nigerian Stock Market.